The process of teaching learning of french as a foreign language in the light of law 10639 - Santos , Petrônio Matias; Soares , Edson Sousa (Seven Editora, 2023)
This paper proposes to present a study about the francophonie, which, according to our investigations, has been defended as a form of cultural cohabitation, respect for diversity, solidarity between peoples. Law No. 10,639/2003 guarantees the teaching of the History of Africa and Afro-Brazilian Culture in all subjects of the Brazilian school curriculum, Elementary and Secondary Education. The didactic materials, also containing cultural elements can contribute to the promotion of education for ethnic-racial relations in the teaching of French as a Foreign Language (FLE). This research aims to investigate how the teaching of culture associated with francophonie and law 10.639/2003 is a teaching that also aims at the education of ethnic-racial relations. This research, characterized as an action-research, of interpretivist character, will be developed in an environment of public language center and, by concluding it, we hope to contribute to the reflection on the insertion of culture in the teaching of languages as a provoking element of reflections, debates, formation of the individual, construction of new social perspectives and also deconstruction of values related to race and prejudices cultivated in our environment. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-129